Ferroelectric and dielectric characteristics of Bi3.25La0.75Ti3O12 thin films prepared by the polymeric precursor method - Simoes, A. Z.; Ramirez, M. A.; Stojanovic, B. D.; Marinkovic, Z.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Vilarinho, P. M. (Trans Tech Publications Ltd, 2006)
The ferroelectric properties and leakage current mechanisms of preferred oriented Bi3.25La0.75Ti3O12 (BLT) thin films deposited on La0.5Sr0.5CoO3 (LSCO) by the polymeric precursor method were investigated. Atomic force microscopy indicates that the deposited films exhibit a dense microstructure with a rather smooth surface morphology. The improved ferroelectric and leakage current characteristics can be ascribed to the plate-like grains of the BLT films.
Keywords: thin films; bismuth titanate; dielectric properties; ferroelectric properties